2016
DOI: 10.1161/strokeaha.116.013722
|View full text |Cite
|
Sign up to set email alerts
|

Risk Profile of Symptomatic Lacunar Stroke Versus Nonlobar Intracerebral Hemorrhage

Abstract: T he term cerebral small vessel disease (SVD) encompasses a wide spectrum of pathological processes affecting the small vessels of the brain, 1 among which, arteriolosclerosis, also known as hypertensive microangiopathy, is the most common. Lacunar strokes (LS) and hemorrhages located in the deep brain regions (nonlobar or deep intracerebral hemorrhage [dICH]) represent the acute symptomatic consequences of this progressive microangiopathy. Because these two phenotypes share the same pathological substrate, 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…It is possible that the micro- and macrovascular effects of diabetes constitute a critical mediator that, in the presence of hypertension, predisposes to a thrombogenic process. This finding is in accordance with prior studies 2 , but contradicts a recent study comparing iCH and LS cases where no difference in the prevalence of diabetes was found 5 .…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the micro- and macrovascular effects of diabetes constitute a critical mediator that, in the presence of hypertension, predisposes to a thrombogenic process. This finding is in accordance with prior studies 2 , but contradicts a recent study comparing iCH and LS cases where no difference in the prevalence of diabetes was found 5 .…”
Section: Discussionsupporting
confidence: 88%
“…In our study, history of hypertension and the specific pressure values (SBP, DBP, PP, and MAP) played a dominant role in dICH, which favored previous findings (7, 8). Contrary to hypertension, diabetes mellitus was associated with SAO stroke, which was also consistent with previous reports (1921).…”
Section: Discussionsupporting
confidence: 77%
“…However, SAO stroke and dICH represent opposite ends of the similar pathological process in cerebral small vessels. It was shown that patients with SAO were older and more likely to have diabetes mellitus and higher cholesterol level, while dICH patients tended to be excessive alcohol consumers and have hypertension (7, 8). However, controversy still remained on other risk factors for cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological changes of small arteries and capillaries are defined as cerebral small vessel disease (CSVD), characterized by age-dependent blood-brain barrier (BBB) breakdown and arteriolosclerosis leading to small vessel occlusions, microbleeds and lacunar infarctions [ 5 7 ]. Recent human cohort studies using magnetic resonance imaging (MRI) challenged the specific associations between lacunar infarct development and hypercholesterolemia [ 8 10 ]. Furthermore, other studies claimed protective effects of hypercholesterolemia preventing from CSVD-related downstream microangiopathic lesions [ 11 12 ].…”
Section: Introductionmentioning
confidence: 99%